Vision and reality in Pacific religion : essays in honour of Niel Gunson - Herda, Phyllis; Reilly, Michael (Michael Patrick Joseph); Hilliard, David, 1941- (Pandanus Books, 2005)
Vision and Reality explores the religious history of the Pacific Islands, examining the indigenisation of Christianity and other faiths.